Consequence Management of a Yield-Producing Nuclear Detonation INCONUS: is NORTHCOM Ready - Phillips, Joseph (2009)
In the event of a nuclear attack in the United States, NORTHCOM would lead the DoD military response. At the moment, however, NORTHCOM is not prepared to provide optimal support in the consequence management of a yield-producing nuclear detonation within the United States. The lack of unity of command between Title 10 and Title 32 forces that would respond to a nuclear disaster will be a critical weakness. The CBRNE (Chemical, Biological, Radiological, Nuclear, and Explosive) Consequence Management Response Force (CCMRF, pronounced "sea smurf") is responsible for NORTHCOM's consequence management response at the tactical level. The transportation requirements for the CCMRF response to a nuclear disaster will be significant and may affect the timeliness of the DoD response. The USMC Chemical, Biological Incident Response Force (CBIRF) in Indian Head, MD provides the search and extract capability in nuclear contaminated areas for the CCMRF, but it is critically undermanned and too centralized. And finally, the length of the reserve mobilization process will need attention in order to provide useful reserve support. The original document contains color images.